Development of A Snakes and Ladders Game-Based Nutrition Education Media to Adderss Anemia in Adolescent Females - Winda Sauci Panjaitan; Kusnandar Kusnandar; Nur Hafidha Hikmayani (Global Health Science Group, 2023)
In 2023, the global prevalence of anemia among female adolescents is projected to reach 32.8%, indicating a persistently high prevalence. The primary cause of anemia is iron deficiency, and its common signs and symptoms include weakness, fatigue, lethargy, tiredness, and a lack of energy which can significantly impact the well-being of individuals. Young women with anemia may experience growth retardation, increased susceptibility to infections, reduced physical fitness, and difficulties in concentration and learning. One strategy to address this issue is the development of a creative nutritional education media that can improve adolescents' knowledge about anemia. Therefore, this study aims to develop a Snakes and Ladders game-based nutritional education media, specifically designed for adolescent females who are at a higher risk of developing anemia. The research follows a research and development approach using the ADDIE model, consisting of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. Both qualitative and quantitative data analyses were employed to analyze the media validity. Quantitatively, the educational media received positive validation scores, with media experts providing an 84,4% rating, material experts rating it at 83,8%, and linguistic experts at 85,2%. The young female respondents in the media trial phase achieved an average knowledge scores of 88% regarding anemia. In conclusion, the nutrition education media based on the popular Snakes and Ladders game is both feasible and effective as an educational tool for anemia education. Further development of the educational media should consider targeting a broader audience, such as pregnant women and nursing mothers